Development and performance evaluation of modified banana chipper - LIJU K; Er. Prince M. V (Guide) (Tavanur 1997 Department of Post-Harvest Technology and Agricultural Processing)
conventional method. in order to eliminate the drudgery involved in chip making and avoid injury to workers, enhance the capacity and to maintain hygiene, an attempt was undertaken at KCAET with the following objectives, to develop a mechanical banana chipper, to evaluate the performance of the machine etc.
Development and performance evaluation of modified banana chipper